2015
DOI: 10.1038/cddis.2014.573
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-141 inhibits tumor growth and metastasis in gastric cancer by directly targeting transcriptional co-activator with PDZ-binding motif, TAZ

Abstract: Gastric cancer (GC) is a biologically heterogeneous disease accompanying various genetic and epigenetic alterations, and the molecular mechanisms underlying this disease are complex and not completely understood. Increasing evidence shows that abnormal microRNA (miRNA) expression is involved in GC tumorigenesis, but the role of specific miRNAs involved in this disease remains elusive. MiR-141 was previously reported to act as tumor suppressors or oncogenes in diverse cancers. However, their accurate expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…Although let-7b upregulation is observed in aged neural stem cells and is associated with the severity of lens opacity during aging [40], we discovered that downregulation of let-7b is an early relapse biomarker, particularly in elderly patients. miR-141 has been reported to inhibit the migration and proliferation of gastric cancer cells [40,41], whereas other studies have shown ); ΔCt = (Ct miR −Ct U6b ), with U6b as the internal control for normalization. a The samples from early relapsed patients showed significantly increased miR-7 expression levels (P = 0.014).…”
Section: Discussionmentioning
confidence: 99%
“…Although let-7b upregulation is observed in aged neural stem cells and is associated with the severity of lens opacity during aging [40], we discovered that downregulation of let-7b is an early relapse biomarker, particularly in elderly patients. miR-141 has been reported to inhibit the migration and proliferation of gastric cancer cells [40,41], whereas other studies have shown ); ΔCt = (Ct miR −Ct U6b ), with U6b as the internal control for normalization. a The samples from early relapsed patients showed significantly increased miR-7 expression levels (P = 0.014).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Zuo et al (2015) found that the expression of miR-141 was significantly reduced in gastric cancer tissues compared with paired adjacent normal tissues. MiR-141 inhibited tumor growth and metastasis in gastric cancer by directly targeting the transcriptional co-activator with PDZ-binding motif, TAZ.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression of miR-141 was significantly correlated with a more aggressive phenotype in clinic [49]. That is to say, miR-141 suppressed in vitro migration and invasion of GC cells.…”
Section: Mir-141 and Tumor Invasion And Metastasismentioning
confidence: 99%
“…Therefore, the miR-141-STAT4 pathway may be exploited in a therapeutic approach for the treatment of H. Pylori related cancers [48]. Functional researches suggested that miR-141 could not only inhibit growth and colony formation but also enhance caspase-3-dependent apoptosis in pancreatic ductal adenocarcinomacells by targeting Yes-associated protein-1 [49]. In pancreatic cancer, another research demonstrated that miR-141 could directly bind to 3′-UTR of mitogenactivated protein kinase isoform 4 to inhibit MAP4K4 expression and lead to the inhibition of cell proliferation [50].…”
Section: Upstream and Downstream Pathways Of Mir-141mentioning
confidence: 99%